Antidiabetic Activity of a Flavonoid-Rich Extract From Sophora davidii (Franch.) Skeels in KK-Ay Mice via Activation of AMP-Activated Protein Kinase - Huang, Yun; Hao, Ji; Tian, Di; Wen, Yanzhang; Zhao, Ping; Chen, Hao; Lv, Yibin; Yang, Xinzhou (Frontiers in Pharmacology, 2018)
The present study was undertaken to investigate the hypoglycemic activity and potential mechanisms of action of a flavonoid-rich extract from Sophora davidii (Franch.) Skeels (SD-FRE) through in vitro and in vivo studies. Four main flavonoids of SD-FRE namely apigenin, maackiain, leachianone A and leachianone B were purified and identified. In vitro, SD-FRE significantly promoted the translocation and expression of glucose transporter 4 (GLUT4) in L6 cells, which was significantly inhibited by Compound C (AMPK inhibitor), but not by Wortmannin (PI3K inhibitor) or Gö6983 (PKC inhibitor). These results indicated that SD-FRE enhanced GLUT4 expression and translocation to the plasma membrane via the AMPK pathway and finally resulted in an increase of glucose uptake. In vivo, using a spontaneously type 2 diabetic model, KK-Ay mice received intragastric administration of SD-FRE for four weeks. As a consequence, SD-FRE significantly alleviated the hyperglycemia, glucose intolerance, insulin resistance and hyperlipidemia in these mice. Hepatic steatosis, islet hypertrophy and larger adipocyte size were observed in KK-Ay mice. However, these pathological changes were effectively relieved by SD-FRE treatment. SD-FRE promoted GLUT4 expression and activated AMPK phosphorylation in insulin target tissues (muscle, adipose tissue and liver) of KK-Ay mice, thus facilitating glucose utilization to ameliorate insulin resistance. Regulation of ACC phosphorylation and PPARγ were also involved in the antidiabetic effects of SD-FRE. Taken together, these findings indicated that SD-FRE has the potential to alleviate type 2 diabetes.